Odpowiedzi

2010-03-14T09:33:29+01:00
-2(2x-1)=x/3
-4x+2=1/3x
-4 1/3 x=-2
-13/3x=-2/*(-3)
13x=6/ 13
x=6/13
2/5(3-x)=-2
6/5-2/5x=-2
-2/5x=-2 5/6
-2/5x=-17/6 /-2/5
x=-17/6*(-5/2)
x=85/12
3/4(2-3x)=-6
3/2-9/4x=-6
-6 3/2=-9/4x
-15/2=-9/4x /*4
-30=-9x /-(9)
x=30/9
x=10/3
2010-03-14T09:40:03+01:00
-2(2x-1)= x/3
-4x+2= x/3 /*3
-3*4x+3*2= 3* x/3
-12x+ 6= x
-13x= 6 /:(-13)
x= - 6/13



2/5(3-x)= -2
1i 1/5 - 2/5x= -2
-2/5x= -2- 1i 1/5
-2/5x= -3 i 1/5 /:(-2/5)
x= 16/5* (- 5/2)
x= 8


3/4(2-3x)= -6
1i 1/2 - 2i 1/4x= -6
-9/4x= -6- 1i1/2
-9/4x= -7i 1/2 /:(-9/4)
x= -15/2* (-4/9)
x= 10/3
x= 3i 1/3